Blossoms of Friendship - Antony Palathinkal (Journal of Dharma, 1977)
The book under review is a collection of Ten Talks by Miss Vimala Thakar and Two discussions conducted by her with young friends from the West at Mount Abu in India, in 1973. The contents of this book revolve around the point that human life is a constant search for authentic existence; and the lion-share of the book is devoted to an explanation of the complex psycho-physical factors which help man in his enquiry. The author’s method is analytic, not dogmatic and authoritarian. True to the title of the book, the lectures contained in this volume have blossomed out of the friendship of a few fellow-enquirers.